1995
DOI: 10.1128/iai.63.7.2409-2417.1995
|View full text |Cite
|
Sign up to set email alerts
|

Clonal relationships among bloodstream isolates of Escherichia coli

Abstract: The clonal relationships among 187 bloodstream isolates of Escherichia coli from 179 patients at Boston, Mass., Long Beach, Calif., and Nairobi, Kenya, were determined by multilocus enzyme electrophoresis (MLEE), analysis of polymorphisms associated with the ribosomal operon (ribotyping), and serotyping. MLEE based on 20 enzymes resolved 101 electrophoretic types (ETs), forming five clusters; ribotyping resolved 56 distinct patterns concordant with the analysis by MLEE. The isolates at each study site formed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…Strains and papG PCR assay. Representatives of each known naturally occurring papG allele configuration, i.e., those of classes I plus III, III, II plus III, and II (13,60), plus several papG-negative strains, were arbitrarily selected from available collections of papG genotyped clinical isolates of E. coli (14,18,21,43,55,59) (Table 2). In addition, because of previously reported phenotypic dis-crepancies between recombinant and wild-type class III strains (12,35), recombinant class III strain P678-54 (pJFK102) (30) was included.…”
Section: Methodsmentioning
confidence: 99%
“…Strains and papG PCR assay. Representatives of each known naturally occurring papG allele configuration, i.e., those of classes I plus III, III, II plus III, and II (13,60), plus several papG-negative strains, were arbitrarily selected from available collections of papG genotyped clinical isolates of E. coli (14,18,21,43,55,59) (Table 2). In addition, because of previously reported phenotypic dis-crepancies between recombinant and wild-type class III strains (12,35), recombinant class III strain P678-54 (pJFK102) (30) was included.…”
Section: Methodsmentioning
confidence: 99%
“…Biochemical and molecular techniques such as multilocus enzyme electrophoresis (MLEE), restriction fragment length polymorphism (RFLP) of rDNA (ribotyping) and DNA profile obtained after the polymerase chain reaction with ERIC primers specific for enterobacterial repetitive intergenic consensus (ERIC-PCR) have been used to identify and characterize distinct bacterial populations and to study the clonal relationships among subgroups inside these populations 1,23,28,30,38,41,47,48,49 .…”
Section: Introductionmentioning
confidence: 99%
“…The extent of recombination within bacterial populations is still controversial, but recent studies suggest that it may vary considerably, leading to population structures that range from highly clonal to non-clonal (Maynard Smith et al, 1993). Escherichia coli (Wang et al, 1993;Desjardins et al, 1995;Maslow et al, 1995), Salmonella enterica (Beltran et al, 1988;Boyd et al, 1996), and encapsulated Haemophilus influenzae are species in which recombination appears to be relatively infrequent, since isoenzyme studies have shown strong linkage disequilibrium between alleles. In these clonal species, the trees constructed using the sequences of different housekeeping genes should be broadly congruent with each other, and with those obtained from isoenzyme data.…”
Section: Introductionmentioning
confidence: 99%